2017
DOI: 10.1016/j.healthplace.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Built environmental correlates of cycling for transport across Europe

Abstract: This cross-sectional study aimed to determine which objective built environmental factors, identified using a virtual neighbourhood audit, were associated with cycling for transport in adults living in five urban regions across Europe. The moderating role of age, gender, socio-economic status and country on these associations was also investigated. Overall, results showed that people living in neighbourhoods with a preponderance of speed limits below 30km/h, many bicycle lanes, with less traffic calming device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
3
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(62 citation statements)
references
References 61 publications
1
55
3
3
Order By: Relevance
“…The Variance Inflation Factors (VIFs) were checked in R with the ‘usdm’ package. All VIFs were low (<2), indicating that multicollinearity was not present [67,68]. …”
Section: Discussionmentioning
confidence: 99%
“…The Variance Inflation Factors (VIFs) were checked in R with the ‘usdm’ package. All VIFs were low (<2), indicating that multicollinearity was not present [67,68]. …”
Section: Discussionmentioning
confidence: 99%
“…Even though length and time taken are important factors for route choice, the data show that greenspace also plays an equally important role, while providing healthier environmental conditions [40,41]. In addition, as roads with little traffic and existing cycle paths are of great importance to the majority, urban transport planning should prioritize cycle route planning along roads and paths other than main roads, through green areas with separate cycle (high)ways where necessary [42]. Some studies have evaluated the positive effects of alternative route choices on lower air pollution exposure [43,44].…”
Section: Tackling the Exposure Awareness Gapmentioning
confidence: 99%
“…Two studies [30,64] found inconsistent results when using different analyzed geographic units. Five studies [25,30,42,58,62] found inconsistent results when using different measurements of AT. One study [48] found inconsistent relationships between land use mix and walking to different destinations.…”
Section: Inconsistent Results From Studies With Different Designsmentioning
confidence: 99%
“…Access to destinations [58] • Access to retail jobs was positively related to the frequency of cycling for transport • Access to retail jobs was negatively related to the participation in cycling for transport [64] • 500-m buffer: access to destination was not related to walking for transport • 1000-m buffer: access to destination was positively related to walking for transport Neighborhood aesthetics [62] • Presence of trees was positively related to the participation in cycling for transport • Presence of trees was negatively related to the duration of cycling for transport…”
Section: Built Environment Factors Reference Resultsmentioning
confidence: 99%
See 1 more Smart Citation